Computed Tomography Appearance of Renal Hybrid Oncocytic/Chromophobe Tumors. Issue 4 (July 2016) - Bhatnagar, Akrita; Rowe, Steven P.; Gorin, Michael A.; Pomper, Martin G.; Fishman, Elliot K.; Allaf, Mohamad E.
Abstract : Objective: A series of renal hybrid oncocytic/chromophobe tumors (HOCTs) was retrospectively assessed for morphologic features and enhancement characteristics by computed tomography (CT). Materials (Subjects) and Methods: Nine patients with pathologically proven HOCTs were identified. These patients harbored a total of 12 lesions. All patients had available preoperative contrast-enhanced CT examinations, although a proportion of the studies had been carried out at outside institutions. The morphologic characteristics and enhancement patterns of each tumor were evaluated systematically. Results: Seventy-eight percent of the patients were men, with a mean age of 62 years. None of the patients had evidence of metastatic disease at the time of surgery. Mean tumor diameter was 4.4 cm. All the lesions were solid and well circumscribed. Calcifications were not seen in any of these masses. Thirty-three percent of the tumors demonstrated a central stellate hypodensity pattern, whereas a further 42% of the tumors demonstrated a heterogenous appearance. Mean attenuation values were 25.7 HU (noncontrast), 77.4 HU (arterial), 124.8 HU (venous), and 76.8 HU (delayed). Tumor-to-cortex ratios for the 2 enhanced phases (arterial and venous) were 0.56 and 0.79, respectively. Conclusions: A series of HOCTs were found on CT to have 2 distinct patterns—a heterogenous enhancement pattern and an "oncocytoma-like" pattern with a central stellate hypodensity. Although the prospective diagnosis of HOCTs on the basis of CT findings is unlikely, an awareness of the existence of these lesions is important as new means of characterizing renal masses on imaging arise.